2018
DOI: 10.1177/0310057x1804600207
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Multifaceted Postoperative Nausea and Vomiting Reduction Strategy on Prophylaxis Administration Amongst Higher-Risk Adult Surgical Patients

Abstract: Postoperative nausea and vomiting (PONV) is a common and distressing problem for patients and increases the burden of care in post-anaesthesia care units (PACU). As such it has been a recent focus for quality improvement. Evidence-based guidelines have demonstrated the benefit of PONV risk stratification and prophylaxis, but may be underutilised in clinical practice. This prospective pre-/post-intervention study was conducted at an adult tertiary hospital in non-cardiac adult surgical patients at higher risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…10,11 High-quality clinical practice guidelines on PONV management have been developed, and they recommend prophylaxis administration based on PONV risk stratification. 3,8,12 However, their actual effects on clinical practice are limited [13][14][15][16] because of several reasons.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 2 more Smart Citations
“…10,11 High-quality clinical practice guidelines on PONV management have been developed, and they recommend prophylaxis administration based on PONV risk stratification. 3,8,12 However, their actual effects on clinical practice are limited [13][14][15][16] because of several reasons.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…3,8,12 However, the implementation of these guidelines in routine clinical practice has been poor. 9,14,16,20,30 Some studies attempted to improve clinicians' compliance with PONV prophylaxis through different interventions, 13,15,20,[30][31][32][33] among which automated reminders were most commonly reported. 13,16,31,33,34 However, the real role about automated reminders remains controversial and is limited in PONV management.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients regard vomiting as the most undesirable complication of anesthesia and qualify it as a more unpleasant sensation than pain [1,2]. The incidence of PONV in adult population is 30% [3], and in high-risk population such as gynecologic and laparoscopic surgery, it can be up to 80% [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…
We read with interest the recent publication by Pym and Ben-Menachem regarding their use of a multifaceted reduction strategy in an effort to reduce the rates of postoperative nausea and vomiting (PONV). 1 The efforts of the authors to implement a quality improvement project in their hospital is admirable, and highlight a growing awareness for the continuous need to re-evaluate and improve upon current practices based on a cycle of feedback and appraisal of evidence, as highlighted by the recent guidelines published by the College. 2 In their discussion, the authors debated the lack of significant increase in prophylaxis prescribing, and a seemingly scant uptake of a promoted guideline on PONV prophylaxis, despite their use of a multifaceted reduction strategy.
…”
mentioning
confidence: 99%